Evaluating the Dimensionality and Invariance of ”Low Self-Control” - Arneklev, Bruce J. (Journal of quantitative criminology, 1999)
According to Gottfredson and Hirschi's (1990) A General Theory ofCrime , all illegal activity is the manifestation of a single underlyingcause. The authors argue that inadequate child-rearing causes individualsto develop a similar type of propensity for criminal and analogousbehavior. Gottfredson and Hirschi label this characteristic“low self-control.” Six dimensions, which can be identified intheir theory, are suggested to comprise a final low self-controltrait. Further, low self-control is proposed to be an invariantcharacteristic (i.e., its form does not change with the age of theindividual or context in which the person resides). In this research, weevaluate these two propositions. First, the six dimensions are measured andused to determine if a multidimensional model can explain another commonfactor—low self-control—in two samples of individuals (fromdifferent locales) with dissimilar mean ages. Second, low self-control inboth samples is tested for invariance. We test the proposed invariance oflow self-control by examining if the parameter values in a model, which isreflective of Gottfredson and Hirschi's conceptualization of thecharacteristic, differ across the two samples of individuals. The resultssupport both of Gottfredson and Hirschi's propositions. Lowself-control does appear to be a multidimensional characteristic whosedimensions represent another common factor. Low self-control also appears tobe an invariant latent trait that members of these two samplespossess. These tests help to clarify Gottfredson and Hirschi'sconceptualization of low self-control.